2012
DOI: 10.1177/1065912911430670
|View full text |Cite
|
Sign up to set email alerts
|

Interrogational Torture

Abstract: Debate about the sources of intelligence leading to bin Laden’s location has revived the question as to whether interrogational torture is effective. Answering this question is a necessary—if not sufficient—condition for any justification of interrogational torture. Given the impossibility of approaching the question empirically, I address it theoretically, asking whether the use of torture to extract information satisfies reasonable expectations about reliability of information as well as normative constraint… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 12 publications
(6 reference statements)
0
7
0
Order By: Relevance
“…Reyes (2007) avers that, during interrogations, methods of torture are used specifically to soften up and break detainees' resistance which will induce them 'to talk'. Like many other scholars such as Bagaric and Clarke (2007), Schiemann (2012), andParry (2003), the IPID investigating officers also argued that, without the use of torture, the investigation process becomes futile. It is for this reason that the use of torture is appraised as a potent and efficacious tool in gaining suspect compliance during an investigation.…”
Section: Acquiring Suspect Compliancementioning
confidence: 86%
See 3 more Smart Citations
“…Reyes (2007) avers that, during interrogations, methods of torture are used specifically to soften up and break detainees' resistance which will induce them 'to talk'. Like many other scholars such as Bagaric and Clarke (2007), Schiemann (2012), andParry (2003), the IPID investigating officers also argued that, without the use of torture, the investigation process becomes futile. It is for this reason that the use of torture is appraised as a potent and efficacious tool in gaining suspect compliance during an investigation.…”
Section: Acquiring Suspect Compliancementioning
confidence: 86%
“…It is thus unsurprising that torture functions "...as an information-gathering device" (Clemens and Grigg 2006) and that it prevails as a perceived efficacious modus operandi to extract information. Recent studies have argued that there is a correlation between torture and the truth (Hajjar 2000;Parry 2003;Schiemann 2012). This notion prompted some of the participants to justify the prevalence of torture although it is outlawed with arguments such as: "You will never, never ever solve your cases if you don't turn on a little bit of heat on the suspect."…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…John Schiemann (2012; has applied mathematical models linked to game theory to see which combinations of interactions between interrogator and detainee produce more effective results. He showed that what he calls the Bush model of interrogation can hardly be justifiable in terms of efficacy.…”
Section: S C I E N T I F I C a R T I C L Ementioning
confidence: 99%